Factors associated with high-risk human papillomavirus test utilization and infection: a population-based study of uninsured and underinsured women - Adana A. M. Llanos; Jennifer Tsui; David Rotter; Lindsey Toler; Antoinette M. Stroup (BMC, 2018)
Abstract Background Current cervical cancer screening guidelines recommend a Pap test every 3 years for women age 21-65 years, or for women 30-65 years who want to lengthen the screening interval, a combination of Pap test and high-risk human papilloma virus testing (co-testing) every 5 years. Little population-based data are available on human papilloma virus test utilization and human papilloma virus infection rates. The objective of this study was to examine the patient-level, cervical cancer screening, and area-level factors associated with human papilloma virus testing and infection among a diverse sample of uninsured and underinsured women enrolled in the New Jersey Cancer Early Education and Detection (NJCEED) Program. Methods We used data for a sample of 50,510 uninsured/underinsured women, age ≥ 29 years, who screened for cervical cancer through NJCEED between January 1, 2009 and December 31, 2015. Multivariable logistic regression models were used to estimate associations between ever having a human papilloma virus test or a positive test result, and individual- (age, race/ethnicity, birthplace) and area-level covariates (% below federal poverty level, % minority, % uninsured), and number of screening visits. Results Only 26.6% (13,440) of the sample had at least one human papilloma virus test. Among women who underwent testing, 13.3% (1792) tested positive for human papilloma virus. Most women who were positive for human papilloma virus (99.4%) had their first test as a co-test. Human papilloma virus test utilization and infection were significantly associated with age, race/ethnicity, birthplace (country), and residential area-level poverty. Rates of human papilloma virus testing and infection also differed significantly across counties in the state of New Jersey. Conclusions These findings suggest that despite access to no-cost cervical cancer screening for eligible women, human papilloma virus test utilization was relatively low among diverse, uninsured and underinsured women in New Jersey, and test utilization and infection were associated with individual-level and area-level factors.